Northernmost record of the pinjalo snapper, Pinjalo pinjalo (Bleeker, 1850) (Perciformes: Lutjanidae) in the northern Indian Ocean: a record from the Iraqi marine waters - Al-Faisal , Abbas J.; Mutlak, Falah M. (Mesopotamian Journal of Marine Sciences, 2023)
One specimens measured 270 mm TL is collected from the deeper waters area inside the marine waters of Iraq in 2021. This record is considered the new northern most record of the lutjanid species Pinjalo pinjalo, where Kuwaiti waters record was the old northernmost extension. Possibilities for the presence of this species further north in the Indian Ocean have provided